2022
DOI: 10.3389/fmed.2022.842002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Epididymis Protein 4 in the Diagnosis and Prognosis of Diseases: An Umbrella Review of Systematic Reviews and Meta-Analyses of Observational Studies

Abstract: BackgroundThe application of human epididymis protein 4 (HE4) in diverse health diseases, especially in cancers, has been extensively studied in recent decades. To summarize the existing evidence of the aforementioned topic, we conducted an umbrella review to systematically evaluate the reliability and strength of evidence regarding the role of HE4 in the diagnostic and prognostic estimate of diverse diseases.MethodsElectronic searches in PubMed, Web of Science, and Embase databases were conducted from incepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
(120 reference statements)
3
7
0
Order By: Relevance
“…Scholars Sun and Mo have reported that lung cancer patients with high HE4 levels have significantly shorter survival times than those with lower levels 28,29 . We conducted a RECIST 1.1 assessment on the treated patients and found that the HE4 levels in the PD group were significantly higher than those of patients in the CR, PR, and SD groups, which confirmed our conjecture and also showed that HE4 can be used as a prognostic monitoring indicator for lung cancer 28 . Furthermore, the serum levels of HE4 in the lung cancer cohort were not influenced by smoking or gender, aligning with the literature 14,15,29,30 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Scholars Sun and Mo have reported that lung cancer patients with high HE4 levels have significantly shorter survival times than those with lower levels 28,29 . We conducted a RECIST 1.1 assessment on the treated patients and found that the HE4 levels in the PD group were significantly higher than those of patients in the CR, PR, and SD groups, which confirmed our conjecture and also showed that HE4 can be used as a prognostic monitoring indicator for lung cancer 28 . Furthermore, the serum levels of HE4 in the lung cancer cohort were not influenced by smoking or gender, aligning with the literature 14,15,29,30 .…”
Section: Discussionsupporting
confidence: 84%
“…Simultaneously, we observed a significant increase in HE4 levels in patients with advanced disease (stages III–IV), speculating that elevated HE4 expression may be an important feature of lung cancer progression. Scholars Sun and Mo have reported that lung cancer patients with high HE4 levels have significantly shorter survival times than those with lower levels 28,29 . We conducted a RECIST 1.1 assessment on the treated patients and found that the HE4 levels in the PD group were significantly higher than those of patients in the CR, PR, and SD groups, which confirmed our conjecture and also showed that HE4 can be used as a prognostic monitoring indicator for lung cancer 28 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition to these insightful research articles, two reviews in this Special Issue highlight the role of the solute carrier family 7 member 11 (SLC7A11) transporter (reviewed by Fantone and colleagues) and human epididymis protein 4 (HE4) (reviewed by Anastasi and colleagues) in ovarian cancer, two important players involved in ferroptosis modulation (SLC7A11) [26,27] and ovarian cancer detection (HE4) [28][29][30], respectively. Another review by Vorderbruggen and colleagues highlighted the role of proteolysis targeting chimeras (PROTACs) in ovarian cancer, reviewing the pharmacodynamic properties of these agents.…”
mentioning
confidence: 99%
“…This constitutes a real challenge to clinicians because, in addition to managing SARD, they have to offer adequate control of comorbidities in a multidisciplinary setting with the aim of improving the quality of life of their patients ( 9 ). Liang et al showed elevated levels of human epididymis protein 4 (HE 4 ), a protein expressed in several tissues and used as a biomarker in ovarian cancer ( 10 ), in patients with rheumatoid arthritis (RA) compared to healthy subjects; those who were positive for HE 4 had a higher prevalence of interstitial lung disease (ILD); these data are the first to identify a correlation between HE 4 levels and ILD.…”
mentioning
confidence: 99%